Di Sela-Sela Laboratorium dan Plot Eksperimen MENGENAL HPLC: PERANANNYA DALAM ANALISA DAN PROSES ISOLASI BAHAN KIMIA ALAM - Tri Murningsih; Chairul Chairul (Research Center for Biology-Indonesian Institute of Sciences, 2000)
The development of method to explore natural chemical product initially from plants were started from the beginning and generously from time to time from the conventional one's until sophisticated equipments.The value of plants as food,cosmetic and medicines resources needs specific instruments and methods for determining the quantity as well as quality of the materials in plants.This paper describe in detail one of the sophisticated equipments commonly used for analyzing and isolating bioactive compounds the so called High Performance Liquid Chromatography (HPLC).